Evaluation of the effectiveness of therapy in degenerative-dystrophic disk diseases - Afanasieva, Inna; Garjum, Lamia (The Ukrainian Scientific Medical Youth Journal, 2023)
the dominant role during the incidence of degenerative-dystrophic changes of the spinal col- umn in the lesion is pain syndrome of varying intensity. The purpose of this study: to evaluate the effec- tiveness of conservative methods of treatment of degenerative-dystrophic disk diseases. The retrospective dynamic study included 107 medical records of outpatients, the average age of patients with degenera- tive-dystrophic disk disease who underwent rehabilitation treatment at Evminov Center for Vertebral Health in the period 2021-2022 was 43.4 ± 4.2. Rehabilitation treatment included personalized kinesitherapy on Evminov Prophylactor (inclined board), Glisson’s Loop, taking non-steroidal anti-inflammatory drugs (NSAIDs) for up to two weeks (appointment depending on the intensity of the pain syndrome) against the background of compliance with the orthopedic regimen and follow-up by a rehabilitologist in dynamics. Depending on the therapy, the examined patients were divided into 3 groups: group I – patients with kine- sitherapy, II – kinesitherapy in combination with non-steroidal anti-inflammatory drugs, III – kinesitherapy with Acetaminophen (respectively: 44 (41.1%)); 33 (30.8%); 30 (28.1%) patients). The duration of taking NSAIDs is 1-2 weeks, and Acetaminophen is 5-7 days. The condition of patients was assessed at the time of the initial visit to Evminov Center and after the first course (3-6 weeks) of rehabilitation measures aimed at decompression of the intervertebral discs. A visual analogue scale was used to measure the intensity of the pain syndrome. According to the results of the study, after 3-6 weeks, there was a positive dynamics of the course in all patients with degenerative-dystrophic disk disease. After 1-2 weeks from the initial visit to the doctor, all patients observed a significant or complete disappearance of pain. Since it is necessary to per- form therapeutic exercises on Evminov Prophylactor only until pain appears, and NSAIDs and Acetamino- phen block the pain perception threshold, kinesitherapy in groups II and III was carried out in a gentle mode (low-amplitude movements), in contrast to group I. After the end of the course of drug therapy (NSAIDs – up to 2 weeks and Acetaminophen – up to 7 days), patients of both groups increased the range of motion on an inclined board, which is confirmed by measuring the intensity of the pain syndrome with a visual analogue scale at certain time intervals. According to the results of the study, patients who received kinesitherapy started strength exercises 1-2 weeks earlier than in groups II and III. Thus, in the rehabilitation treatment of degenerative-dystrophic disk disease with pain syndrome of varying intensity, it is necessary to include kinesitherapy on Evminov Prophylactor, which, 1-2 weeks earlier than when combined with non-steroidal anti-inflammatory drugs or Acetaminophen, allows to get a positive effect, first of all regarding pain.